A metaphorical Interpretation of Great Moments of Passion of Some Characters in Novel Wuthering Heights - Ahmed Ali Ardab, Imad (Gezira Journal of Educational Sciences and Humanities; Vol 17 No 1 (2020), 2020)
The aim of the study is to endeavor to add more readings of the novel "Wuthering Heights" by Emily Bronte through highlighting the importance of figurative language particularly by analysis metaphors included in the text of the novel. Thus this paper attempts to envision more readings of figurative language and thereby links the reaction and behavior of some characters through their speech environment with each other and therefore interpreting each situation due to great moments of passion that characters have passed through. The study adopts descriptive analytical method. One of the most important findings of the study is the use of metaphors gives language much depth and significance. In addition the study recommends that figurative language as metaphors and other rhetorical expressions should be taught at early stages for students who learn English language.